The Representation of Women’s Emancipation in Kevin Kwan’s Crazy Rich Asians : A Liberal Feminist Perspective - Alvina Ryan Fatiha; Maria Johana Ari Widayanti (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study explored the portrayal of women’s emancipation through the character of Goh Peik Lin in Kevin Kwan’s novel Crazy Rich Asians. The research addressed the issue of limited representation of empowered female characters in contemporary literature and aimed to analyze how Peik Lin embodied women’s empowerment within a modern patriarchal context. Using a qualitative descriptive method and liberal feminist theory as the framework, the study examined Peik Lin’s independence, confidence, and equality with men, particularly through her education, career, and lifestyle choices. The analysis also highlighted her solidarity with other women, especially her friendship with the protagonist, Rachel Chu. The findings suggested that Peik Lin represented liberal feminist ideals and challenged traditional gender roles in modern fiction. The study concluded that diverse female perspectives in literature were essential for understanding gender dynamics and encouraged further research on women’s representation across different cultures and genres.